On the chiral expansion of vector meson masses - R. Bavontaweepanya (2019)
© 2018 authors. Published by the American Physical Society. We study the chiral expansion of meson masses and decay constants using a chiral Lagrangian that was constructed previously based on the hadrogenesis conjecture. The one-loop self-energies of the Goldstone bosons and vector mesons are evaluated. It is illustrated that a order-by-order renormalizable effective field theory arises once specific conditions on the low-energy constants are imposed. For the case where the hadrogenesis mass gap scale ΛHG is substantially larger than the chiral symmetry breaking scale Λχ a partial summation scheme is required. All terms proportional to (M/Λχ)n can be summed by a suitable renormalization, where M is the chiral and large-Nc limit of the vector meson masses in QCD. The size of loop effects from vector meson degrees of freedom is illustrated for physical quark masses. Naturally sized effects are observed that have significant impact on the chiral structure of low-energy QCD with three light flavors.